Rotational Thromboelastometry (ROTEM)-guided Diagnosis and Management of Amniotic Fluid Embolism. Issue 1 (March 2020) - Loughran, J.A.; Kitchen, T.L.; Sindhakar, S.; Ashraf, M.; Awad, M.; Kealaher, E.J.
Abstract : ( Int J Obstet Anesth . 2019;38:127–145) Amniotic fluid embolism (AFE) is rare but can be deadly, affecting 0.35 of 100, 000 maternities in the United Kingdom. Diagnosis can be challenging and relies on exclusion, as this condition lacks special clinical features. Disseminated intravascular coagulation usually occurs in women with AFE and can lead to major postpartum hemorrhage. There has been increasing utilization of point-of-care viscoelastometric testing, including rotational thromboelastometry (ROTEM), during obstetric hemorrhage. This case report described a case of AFE in which ROTEM testing guided patient management.